Inovasi Produk, Persepsi Harga, dan e-WOM terhadap Minat Beli Produk Glad2Glow di E-commerce Shopee - Indriani, Inez Faridah; Hadi, Solikhul (Jurnal Ekonomi dan Bisnis Islam, 2025)
AbstractDriven by fierce competition among beauty products on e-commerce platforms, companies are required to develop strategies to maintain their existence and meet consumer preferences. This study aims to examine the influence of product innovation, price perception, and electronic word of mouth on the purchase intention of Glad2Glow products on Shopee e-commerce. A quantitative method approach was applied in this study. Generation Z in Kudus Regency who use Glad2Glow products became the research population. The accidental sampling technique was used to determine a sample of 96 respondents. Research data was obtained by distributing questionnaires and SPSS 25 as a data processing tool. The results of the study show that product innovation affects purchase interest based on the calculated t value > table t (4.036 > 1.986), price perception affects purchase intention based on the t-value > t-table (2.575 > 1.986), and electronic word of mouth affects purchase intention based on the t-value > t-table (3.746 > 1.986). This study concludes that product innovation, price perception, and electronic word of mouth play an important role in increasing purchase intention.Keywords: Product Innovation; Price Perception; e-WOM; Purchase Intention. AbstrakPesatnya persaingan produk kecantikan pada e-commerce, menuntut perusahaan mengatur strategi dalam mempertahankan eksistensi dan memenuhi preferensi konsumen. Studi ini bertujuan untuk mengkaji pengaruh inovasi produk, persepsi harga, serta electronic word of mouth terhadap minat beli produk Glad2Glow di e-commerce Shopee. Metode kuantitatif diterapkan dalam penelitian ini. Generasi Z di Kabupaten Kudus pengguna produk Glad2Glow menjadi populasi penelitian ini. Teknik accidental sampling guna menentukan sampel yang berjumlah 96 responden. Data penelitian diperoleh dengan mendistribusikan kuesioner dan SPSS 25 sebagai alat pengolahan data. Hasil penelitian yakni, inovasi produk berpengaruh terhadap minat beli berdasarkan nilai t hitung > t tabel (4.036 > 1.986), persepsi harga berpengaruh terhadap minat beli berdasarkan nilai t hitung > t tabel (2.575 > 1.986), serta electronic word of mouth berpengaruh terhadap minat beli berdasarkan nilai t hitung > t tabel (3.746 > 1.986). Dalam studi ini, menyimpulkan bahwa inovasi produk, persepsi harga, serta electronic word of mouth berperan penting dalam meningkatkan minat beli.Kata Kunci: Inovasi Produk; Persepsi Harga; e-WOM; Minat Beli.